2008
DOI: 10.1051/vetres:2008036
|View full text |Cite
|
Sign up to set email alerts
|

Bartonellaspecies detection in captive, stranded and free-ranging cetaceans

Abstract: -We present prevalence of Bartonella spp. for multiple cohorts of wild and captive cetaceans. One hundred and six cetaceans including 86 bottlenose dolphins (71 free-ranging, 14 captive in a facility with a dolphin experiencing debility of unknown origin, 1 stranded), 11 striped dolphins, 4 harbor porpoises, 3 Risso's dolphins, 1 dwarf sperm whale and 1 pygmy sperm whale (all stranded) were sampled. Whole blood (n = 95 live animals) and tissues (n = 15 freshly dead animals) were screened by PCR (n = 106 animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 37 publications
(52 reference statements)
0
26
0
Order By: Relevance
“…[15, 24]) rests upon the isolation of single clades from humans diagnosed by gene sequences which are prone to recombination. Similarly, B. henselae (cat and human parasite transmitted by fleas) has been recorded from marine mammals, transmitted by Cyamus [16]; the use of a wider range of loci in this work might have clarified the exact strains capable of such an ecologically diverse zoonosis. The present work makes it clear that this approach is both unreliable and potentially highly misleading, and the use of these sequences, especially the 16S RNA marker, for diagnostic purposes should be undertaken only with extreme caution.…”
Section: Discussionmentioning
confidence: 96%
“…[15, 24]) rests upon the isolation of single clades from humans diagnosed by gene sequences which are prone to recombination. Similarly, B. henselae (cat and human parasite transmitted by fleas) has been recorded from marine mammals, transmitted by Cyamus [16]; the use of a wider range of loci in this work might have clarified the exact strains capable of such an ecologically diverse zoonosis. The present work makes it clear that this approach is both unreliable and potentially highly misleading, and the use of these sequences, especially the 16S RNA marker, for diagnostic purposes should be undertaken only with extreme caution.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, it has been demonstrated that bovines and other animals are capable of generating antibodies against deep determinants of LPS such as the core and lipid A moieties (41), which are shared by other Alphaproteobacteria related to Brucella (8,50). Since Alphaproteobacteria, such as Bartonella species, also infect odontocetes (23), cross-reactions against these deep LPS epitopes may arise. The relatively higher specificity of cELISA seems to be linked to the competing monoclonal antibody which specifically recognizes the C epitope of the LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Cat fleas, Ctenocephalides felis, are thought to be the sole or primary vector for B. henselae transmission to pets and potentially people (Bouhsira et al 2013). To date, Bh DNA has been PCR amplified from the blood of cats, dogs, feral swine, cattle, horses, sea turtles, wild cats, and several marine mammal species (Harms et al 2008, Cherry et al 2009, Chomel and Kasten 2010, Psaroulaki et al 2010, Beard et al 2011, Cherry et al 2012, Girard et al 2012.…”
Section: Introductionmentioning
confidence: 99%